Visual evoked potentials during the early phase of optic nerve compression in the orbital cavity - Janáky, M; Benedek, G (Documenta ophthalmologica, 1992)
We obtained case histories and electrophysiologic recordings from four patients with transient vision impairment due to acute orbital compression. The visual evoked potentials (VEPs) displayed alterations that depended on the size and consistency of the compressing pathology and also on the duration of the compression. This study provides evidence of the utility of the VEP in the assessment of the severity and reversibility of optic nerve lesions. The case histories also emphasized the necessity to elucidate the pathologic process of compressive lesions of the optic nerve.